The Impact of Team Performance and Work Motivation on Company Performance - Karismayanti, Widi; Nurvasya, Fadila (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2025)
This research aims to analyze the effects of work motivation and team performance on employee and company performance. A quantitative approach using primary data from questionnaires was conducted with employees from Bank BRI. The study reveals that team performance has a significant influence on company performance. High team effectiveness is crucial for enhancing overall business outcomes. Additionally, work motivation plays a pivotal role, as motivated individuals foster creativity, contributing to improved organizational success. Regression analysis indicates that both team performance and work motivation significantly impact company performance, with team performance contributing 37.9% to organizational outcomes. The research concludes that fostering a collaborative team environment and maintaining high motivation levels are essential for driving company performance. The study emphasizes the interdependence of these factors, offering valuable insights into the dynamics of workforce effectiveness.